Depressive symptoms as potential moderator and mediator : rejection sensitivity and emotional recognition of facial expression in adults who are pursuing tertiary education - Zabri, Dalili Zahiah (2021)
Everyone experiences social interaction with human beings at any point of life. Social interaction may lead to social rejection and considered normal to be experienced at any point of relationship. Different people tend to have different level of rejection sensitivity level. Much of the rejection sensitivity research conducted within Western countries and not Asian countries. Previous research found a relationship between rejection sensitivity level and depression (Kraines & Wells , 2017). Previous research shows there is a positive relationship between depression and rejection sensitivity level (Kraines & Wells , 2017). Relationship between depression and emotion recognition were also found in previous studies (Byrne, Norris, & Worthy, 2016). Previous research shows that there is a negative relationship between depression and emotion recognition (Byrne, Norris, & Worthy, 2016). This research investigates whether research findings collected within Western population is in line with Asian Population. Based on the relationship found in previous research studies, I further tested if there is a relationship between rejection sensitivity and emotional recognition of facial expression with depressive symptoms as a potential moderator and mediator of the relationship. A total of 85 participants covering male and female adults who are pursuing tertiary education in Malaysia have participated in this correlational study by completing a 30 minutes face to face session. All participants completed 2 self – report questionnaires and 1 computerized test in a single session. The difference of rejection sensitivity level between male and female adults who are pursuing tertiary education was explored using independent t – test. Results show there were no significant difference between male and female adults in rejection sensitivity level. The relationship of rejection sensitivity level and emotional recognition of facial expression was also explored using correlation. There was no significant relationship found between rejection sensitivity level and emotional recognition. Lastly, PROCESS in SPSS was used to analyze if depressive symptom moderates or mediates the relationship of rejection sensitivity level and emotional recognition. Depressive symptom was found to be not significant in moderating or mediating the strength of relationship between rejection sensitivity level and emotional recognition of facial expression.